2004
DOI: 10.1017/s0016672304006986
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variation among divergent populations of stalk-eyed flies, genus Cyrtodiopsis

Abstract: SummaryMicrosatellite primers are often developed in one species and used to assess neutral variability in related species. Such analyses may be confounded by ascertainment bias (i.e. a decline in amplification success and allelic variability with increasing genetic distance from the source of the microsatellites). In addition, other factors, such as the size of the microsatellite, whether it consists of perfect or interrupted tandem repeats, and whether it is autosomal or X-linked, can affect variation. To te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 49 publications
(46 reference statements)
4
57
0
Order By: Relevance
“…Weak amplifications could result because of low quality of DNA (Nagamitsu et al 2001), annealing temperature, variation in PCR reagent components used in various studies and different species affinities. Previous studies that carefully examined the results of cross-amplification often found limitations to the approach, including loss of the internal repeat (Gutierrez et al 2005), disruption of the repeat structure (Shao et al 2005), increased rate of mutation in the flanking regions (González-Martínez et al 2004), and increased levels of null alleles (Wright et al 2004). Detecting the loss of the internal repeat requires direct DNA sequencing of the fragments, particularly when the repeat originally composed only a small fraction of the entire fragment length.…”
Section: Discussionmentioning
confidence: 99%
“…Weak amplifications could result because of low quality of DNA (Nagamitsu et al 2001), annealing temperature, variation in PCR reagent components used in various studies and different species affinities. Previous studies that carefully examined the results of cross-amplification often found limitations to the approach, including loss of the internal repeat (Gutierrez et al 2005), disruption of the repeat structure (Shao et al 2005), increased rate of mutation in the flanking regions (González-Martínez et al 2004), and increased levels of null alleles (Wright et al 2004). Detecting the loss of the internal repeat requires direct DNA sequencing of the fragments, particularly when the repeat originally composed only a small fraction of the entire fragment length.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, for instance, that meiotic drive causes segregation distortions in mice (Morita et al, 1992;Futuyma, 2005) or in the dipteran Cyrtodiopsis sp. (Wright et al, 2004). Some of these mechanisms may have been also responsible for the conservation of introgressed ITS rDNA alleles in Daphnia.…”
Section: Its-rflpmentioning
confidence: 99%
“…We screened 52 microsatellite markers described elsewhere (Wright et al 2004) to identify 24 informative markers. We used fluorescently labelled primers in 5.5 mL PCR reactions (Wright et al 2004) to amplify four X-linked loci for all 1228 F2 flies from both crosses and 20 autosomal loci for 738 flies from the experimental cross.…”
Section: (A) Experimental Crossesmentioning
confidence: 99%
“…The corresponding X-linked QTL in females explained 9% of eye span variation. Data from the control cross revealed two X-linked QTL in males, which 95B 382 415 398 277 262Z 262Y 217A 301 39 90 480 249 116 402b 395 395 125 54 244 125 a Letters refer to alleles at four X-linked microsatellite loci (Wright et al 2004): ms-54 (AZ160 bp, BZ162 bp), ms-125 (AZ148 bp, BZ153 bp), ms-244 (AZ226 bp, BZ236 bp), and ms-395 (AZ 202 bp, BZ216 bp, CZ238 bp), respectively. explained 8 and 13% of eye span variation, and no significant QTL for females (figure 2).…”
Section: (D) Linkage and Qtl Analysismentioning
confidence: 99%